(3ZGjI GdebUO aj RhGFO GdeSfO (B( (3eSfO CMeO (B)s - (3Ydj Hf CHj HcQ Hf SdjeGf GdgjKej, CHh GdMSf, fhQ GdOjf, GdeUQj GdbGgQj,J (B807 (3g` s ((3ecI GdeTQaI s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3aPcQJ ajgG eG CfaQO GdEeGe CMeO QVi Gddg Yfg ef MOjK HJeGeg hSejJg ZGjI GdebUO ai RhGFO GdeSfO s
(3BNQgG (B:s
(3Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B" (3eG ef EfSGf jchf ai eLdS ajbhd Mjf jQjO Cf jbhe SHMGfc Gddge hHMec dG Edg EdG CfJ GSJZaQc hCJhH Edjc EdG ZaQ dg eG cGf ai Pdc GdeLdS GdMeO ddg Ydi cd MGd s
(3HChdgG agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B45s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs